The Management of Orbital Roof Fractures and Defects: A Review. Issue 1 (January 2022) - Sandhu, Pavandeep Singh; Bucur, Sorin; Good, Catriona; Cutler, Mark; Rajak, Saul
Abstract : Purpose: To explore the anatomy, etiopathogenesis, diagnosis and classification, current evidence on intervention and the surgical management of orbital roof fractures and defects (ORFD) for oculoplastic surgeons presented with such cases. Methods: A review of the current literature through the MEDLINE database using the following search terms: "orbital roof fracture (+treatment/management), " "orbital roof defect (+treatment/management), " "orbital roof erosion (+treatment/management), " "orbital roof repair, " "orbital roof, " "orbital fracture, " "pediatric orbital roof (defect/fracture/erosion), " "orbital anatomy, " and "orbital roof anatomy" was conducted. As relatively little has been published on this topic, inclusion criteria were broad and peer-reviewed articles judged to be of clinical importance, relevant to the aims of this review, were included. Non-English abstracts were also included if relevant. Year of publication was not a strict exclusion criterion, and older articles were judged for their suitability based on clinical importance and relevance to current practice. Additional references were obtained from citations in key articles and recommendations from the coauthors based on their areas of expertise. Results: The etiopathogenesis of ORFD varies. Classification systems have been formulated to guide management decisions and can range from conservative management to complex neurosurgery. Eyelid approaches have also been described. This review provides a summary of the evidence for each and a management framework oculoplastic surgeons can use when presented with ORFD. Conclusion: Oculoplastic surgeons can be involved, either alone or as part of a multidisciplinary team, in the management of ORFD, and for some, conduct orbital approach reconstructive surgery. Abstract : Orbital roof fractures and defects are rare and often complicated, but with a comprehensive understanding of the causes, natural history, and treatment options, they can be managed appropriately by oculoplastic surgeons.